Since you've been gone - Matson, Morgan (Simon & Schuster Books for Young Readers, 2014)
Quiet Emily's sociable and daring best friend, Sloane, has disappeared leaving nothing but a random list of bizarre tasks for her to complete, but with unexpected help from popular classmate Frank Porter, Emily gives them a try.